1982
DOI: 10.1002/1097-4679(198210)38:4<793::aid-jclp2270380417>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Racial influences on intelligence and personality measures of people who commit murder

Abstract: Examined a sample of murderers (N = 137) (91 white and 46 black offenders) for racial differences on intelligence (both verbal and nonverbal) and personality measures. Black offenders scored significantly lower than white offenders on both verbal and nonverbal intelligence as well as on the SI scale of the MMPI. However, they scored higher on the MA scale. Overall, the intelligence measures discriminated better between black and white offenders than personality measures. Implications for future research and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For example, Megargee and Bohn () found that men who have been incarcerated for more than 2 years showed elevations in the dimensions Pd , Sc , and Ma of the MMPI. Additionally, intelligence quotient, social status, and occupational status correlations influence the values reached in inmate population personality profiles (Holcomb & Adams, ; Holcomb, Adams, & Ponder, ; McDonald & Paitich, ). Culture and nationality are also sources of variability in the criminal personality (Boscán et al ., ; Catalá‐Miñana, Walker, Bowen, & Lila, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Megargee and Bohn () found that men who have been incarcerated for more than 2 years showed elevations in the dimensions Pd , Sc , and Ma of the MMPI. Additionally, intelligence quotient, social status, and occupational status correlations influence the values reached in inmate population personality profiles (Holcomb & Adams, ; Holcomb, Adams, & Ponder, ; McDonald & Paitich, ). Culture and nationality are also sources of variability in the criminal personality (Boscán et al ., ; Catalá‐Miñana, Walker, Bowen, & Lila, ).…”
Section: Discussionmentioning
confidence: 99%
“…In studying race, IQ, and the MMPI, Rosenblatt and Pritchard (1978) found Gynther's (1972) black versus white differences only among groups with IQs below 93 on the Wechsler Adult Intelligence Scale (WAIS). Similarly, Holcomb and his associates found that the Gynther pattern of racial differences was eliminated when Peabody and Revised Beta IQs were used as covariates (Holcomb & Adams, 1982Holcomb, Adams, & Ponder, 1984). When education level was examined, blacks were found to score higher than whites on Pa and 5c, but only among groups with fewer than 12 years of schooling (Davis, Beck, & Ryan, 1973;Davis & Jones, 1974;Davis, 1975).…”
Section: Mmpi Minority Differences and Moderating Influencesmentioning
confidence: 93%
“…These findings were similar to some of the differences that have been reported in the way that the Black population scores on the MMPI. For example, there are indications that Black psychiatric patients tend to score higher on the Psychopathic Deviate scale (Davis et al, 1973), the Schizophrenia scale (Butcher et al, 1983;Costello et al, 1973;Costello et al, 1972;Davis et al, 1973;Genther &Graham, 1976;Miller et al, 1968;Miller et al, 1961), and the Hypomania scale (Butcher et al, 1983;Costello et al, 1972;Genther &Graham, 1976;Holcomb & Adams, 1982;Miller er al., 1968;Miller et al, 1961), whereas Blacks may be inclined to obtain a lower score on the Masculinity-Femininity scale (McCreary & Padilla, 1977). Ir would appear that these MMPI scales measure similar characteristics to those mentioned in the previous paragraph as characterizing rhe differences found with the MCMI.…”
Section: )mentioning
confidence: 99%